HCV Protease Inhibitory, Cytotoxic and Apoptosis-Inducing Effects of Oleanolic Acid Derivatives - Chao-Mei Ma; Xiu-Hong Wu; Masao Hattori; Xi-Jun Wang; Yoshihiro Kano (Frontiers Media S.A., 2009)
Purpose: To evaluate oleanolic acid derivatives on liver disease related bioactivities, 29 oleanolic acid derivatives of several series were tested for their inhibitory activity on hepatitis C viral protease and for their cytotoxic effects on Hep G2 cells. Results: The amino derivatives showed potent cytotoxicity, among which, the beta-amino isomer exhibited more distinct cytotoxicity than the alpha-isomer. The cytotoxicity of hemiesters and hemiamides varied as the chain lengths varied. The oxalic and malonic hemiesters showed weaker cytototoxicity than oleanolic acid, while those with longer chain lengths showed higher cytotoxicity. Contrary to the cytotoxic activity, the free amino derivatives showed little inhibitory activity on HCV protease. All the hemiesters and hemiamides showed high activity against HCV protease. Conclusion: The results suggest that adding free amino group(s) to the skeletons of triterpenes may be an effective way of synthesis of anti-tumor compounds. Adding acidic groups to triterpene skeletons may be an effective way for producing anti-viral compounds.